Investigating accountability of public police in the private employment realm - Zaia, Mathew (International journal of law, crime and justice, 2019)
Paid detail police work has grown in recent years across municipal/local and state/provincial jurisdictions in the United States and Canada, but not without controversy. Using Stenning's (2000) accountability framework for private and public police, we consider how and the extent to which the private employment of public police is regulated and rendered accountable. To accomplish this, we draw on interviews with 63 employers of paid detail as well as police officers, policies collected through freedom of information requests from 30 North American police departments about paid detail procedures as well as logs, and media coverage of paid detail issues. We found incredible variation in how paid detail is regulated, as well as many instances where accountability and oversight are lacking. After examining the consequences of ineffective or absent accountability mechanisms, we suggest a more uniform approach to paid detail standards. We conclude by discussing future research about paid detail regulation and policy.